Comparison of Adherence and CD4 counts of HIV patients on various ART Regimens - Sachidananda Adiga; Usha Adiga; BN Malawadi (International Journal of Medical Research and Review, 2016)
Introduction: Inspite of HAART, it has been found that viral replication persists even when viral load is undetectable. Adherence has been reported to be positively associated with CD4 count in various settings. Objectives of our study were comparison of basal CD4 count of HIV patients on various ART regimens with that at six months and one year as well as finding correlation between percentage adherence to ART and CD4 counts at six months and one year. We also aimed to compare percentage adherence and CD4 counts of patients on various ART regimens.Methodology: A retrospective observational study was conducted on 63 HIV patients, receiving four antiretroviral regimens (AZT/3TC/NVP, AZT/3TC/EFV, d4T/3TC/NVP and d4T / 3TC / EFV). Patient demography, drug regimen, baseline CD4 counts, serial CD4 counts (every six months), and adherence to ART (monthly) were recorded. Comparison of basal CD4 counts with that at six months and one year was done. Comparison of CD4 count and adherence were done between the groups.Results: An extremely significant elevation was seen in CD4 counts at six months and at one year (p < 0.0001). Linear regression showed a significant positive correlation (p = 0.037) between adherence and CD4 counts at one year. There was no significant difference in percentage adherence and CD4 counts between four groups.Conclusion: We conclude that optimal CD4 levels were obtained in patients on all four different regimens. However percentage adherence was suboptimal in all groups which caution to take appropriate measures to achieve optimal drug adherence.